Vulnerable populations during COVID-19 response: Health-related quality of life among Chinese population and its influence due to socio-demographic factors and loneliness - Wong, Eliza Lai-Yi; Li, Jia; Yuen, Shannon; Lai, Angel Hor-Yan; Cheung, Annie Wai-Ling; Yau, Peter Sen-Yung; Yeoh, Eng-Kiong (Frontiers in Public Health, 2022)
Background: Infection control policy affected people’s well-being during the COVID-19 pandemic, especially those vulnerable population. This study aimed to explore the factors, including socio-demographic characteristics, loneliness, and the interaction between them, associated with health-related quality of life (HRQoL) among the Hong Kong (HK) Chinese population under the pandemic. Methods: A cross-sectional questionnaire survey (301 online and 202 in-person) was conducted between June and December 2020 among the adult Chinese population during the 2nd wave of COVID-19 in HK. HRQoL was measured by Hong Kong validated EQ-5D-5L instrument (EQ-5D-5L HK). Loneliness was measured by a single item question regarding the frequency of the participant reporting feeling lonely and their subjective social status (SSS was measured by the MacArthur Scale of Subjective Social Status. A series of Tobit regressions were conducted. The interaction terms between socio-demographics and loneliness were also examined to decide their associations with HRQoL. Results: A total of 503 responses were collected. The level of HRQoL of the respondents was significantly lower than the refer norms profile among local general population. The findings identified that a younger age, single, a higher subjective social status, and a lower level of loneliness were significantly associated with better HRQoL. Moreover, age and marital status were significant moderators in the relationship between loneliness and HRQoL. Conclusions: The present study found that some groups of population groups may face additional vulnerabilities during the pandemic in terms of declined HRQoL. Therefore, reducing loneliness can be protective of the HRQoL during the pandemic, especially among older people. This article provides useful information for policy-makers to design and promote effective services or provide education to improve the connection of people and recover from the global pandemic.